Poverty alleviation and inequality of rural economics in Indonesia - IIlham, IIlham; Kadir Arno, Abd.; Thaha, Hamdani (Technium Social Sciences Journal, 2022)
This article aims to provide an overview of poverty alleviation and economic inequality in rural areas in Indonesia. To provide this description, the analysis building in the article will attempt to articulate some of the themes of poverty alleviation programs by data reduction, triangulation of the results of the article and then a presentation of data in the form of narrative texts. The conclusion from the findings of this article is that the program that has been carried out has reduced the amount of poverty nationally quantitatively. However, it should be noted that in poverty alleviation programs don't just prioritize quantitative measures in terms of ithe inumber iof ipoor ipeople, because ithe qualitative phenomena iof ipoverty ithat occur in ithe field are not explored. Therefore a qualitative (subjective) approach is needed to complete and explore non-economic variables that influence poverty assessments.